2007
DOI: 10.1007/s00198-007-0388-y
|View full text |Cite
|
Sign up to set email alerts
|

A computer-based measure of irregularity in vertebral alignment is a BMD-independent predictor of fracture risk in postmenopausal women

Abstract: Our results suggest that the herein introduced simple measure of irregularities in vertebral alignment could provide useful supplement to the currently used diagnostic tools of fracture prediction in elderly women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Finally, we report results of the main experiment on the full Pettersen [25] dataset and compare to results achieved on the reduced dataset (see page 7) used throughout.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we report results of the main experiment on the full Pettersen [25] dataset and compare to results achieved on the reduced dataset (see page 7) used throughout.…”
Section: Discussionmentioning
confidence: 99%
“…The primary utility of the fracture assessment was to establish baseline and followup fracture presence. These readings were used to identify the case (n=36) and controls group (n=108) in the paper by Pettersen [25] in which the fracture risk predictive power of a computer-based measure of curvature irregularity was investigated. The case and control groups in this study were specifically selected as subsets of the Pettersen's case and control group as described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that irregularity in vertebral alignment or spine curvature as can be observed on lateral X-rays is associated with known risk factors for future fractures such as prevalent fractures and low bone mineral density (BMD) [5,6], as well as with future fractures independent of the main risk factors [7]. These studies based their analysis on simple measures of vertebral heights or circles drawn through vertebral body center points and aim at capturing the known characteristics of deformed spines in the hope that these measures may also be suited for early diagnosis and prediction of future deformity.…”
Section: Introductionmentioning
confidence: 99%